Isotherm and Kinetics Adsorption of Ammonium using Cocopeat Biochar Activated - Meta Fitri Rizkiana; Lilis Nurhasanah; Nanda Ayudiyah Andriani; Bekti Palupi; Boy Arief Fachri; Istiqomah Rahmawati; Helda Wika Amini; Endar Hidayat (CHEESA: Chemical Engineering Research Articles, 2025)
Nitrogen recovery from wastewater is capable of preventing eutrophication, offering economic benefits, and reducing carbon footprint from synthetic fertilizer production. Biochar has been explored as adsorbent for ammonium (NH??) removal. Therefore, this study aimed to investigate the potential of biochar derived from cocopeat as adsorbent for NH?? removal. Cocopeat was modified by potassium hydroxide (KOH) and pyrolyzed at 500°C for 2 h to produce activated biochar. Kinetics and isotherm studies were conducted to examine adsorption mechanisms. Fourier Transform Infrared (FTIR) data showed that the resulting biochar after activation and adsorption contained hydroxyl OH and CO groups, while a new NH band confirmed the interaction with NH?? ions. Biochar adsorbed NH?? ions with a maximum capacity of 0.3078?mg/g. FTIR spectra showed shifts and changes in the intensity of functional group bands, confirming the interaction between NH?? ion and the active sites on biochar surface. Adsorption followed Langmuir isotherm and pseudo-first-order kinetics model, with an optimal contact time of 5 h. These results suggested that cocopeat-based biochar had potential as an effective NH?? adsorbent.